Hubungan Antara Kecerdasan Emosional dan Parental Bonding terhadap Dark Triad of Personality Pada Remaja - Mergina, Sindi; Widyorini, Endang; Roswita, Maria Yang (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Adolescence contributes to the formation of personality in a person. Violence against adolescents is also a national problem in Indonesia today. Actions carried out by adolescents who are also students refer to impulsive behavior, shallow feelings, recklessness, as well as superiority and hostility which refer to the dark triad of personality. One of the factors that influence the dark triad of personality is emotional intelligence. Another factor that influences the dark triad of personality is the environment. Family is one of the environmental conditions that can contribute to the formation of one's personality so that bonding from parents contributes to adolescent behavior. This study aims to determine the relationship between emotional intelligence and parental bonding to the dark triad of personality in students at X High School in the city of Semarang. This research method uses a correlational quantitative approach with a total of 352 participants. The measuring instruments used in this study were the short dark triad (SD3), the parental bonding instrument (PBI), and the Schutte Emotional Intelligence Scale (SEIS). The analysis carried out in this study used multiple regression analysis with SPSS version 26. The results in this study found that there was an effect of the variables of emotional intelligence and parental bonding simultaneously on the dark triad of personality in X High School students in the city of Semarang.